Hypoxia and aging: molecular mechanisms, diseases, and therapeutic targets - Ayesha Nisar; Sawar Khan; Wen Li; Li Hu; Priyadarshani Nadeeshika Samarawickrama; Naheemat Modupeola Gold; Meiting Zi; Sardar Azhar Mehmood; Jiarong Miao; Yonghan He (MedComm, 2024)
Abstract Aging is a complex biological process characterized by the gradual decline of cellular functions, increased susceptibility to diseases, and impaired stress responses. Hypoxia, defined as reduced oxygen availability, is a critical factor that influences aging through molecular pathways involving hypoxia‐inducible factors (HIFs), oxidative stress, inflammation, and epigenetic modifications. This review explores the interconnected roles of hypoxia in aging, highlighting how hypoxic conditions exacerbate cellular damage, promote senescence, and contribute to age‐related pathologies, including cardiovascular diseases, neurodegenerative disorders, cancer, metabolic dysfunctions, and pulmonary conditions. By examining the molecular mechanisms linking hypoxia to aging, we identify key pathways that serve as potential therapeutic targets. Emerging interventions such as HIF modulators, antioxidants, senolytics, and lifestyle modifications hold promise in mitigating the adverse effects of hypoxia on aging tissues. However, challenges such as the heterogeneity of aging, lack of reliable biomarkers, and safety concerns regarding hypoxia‐targeted therapies remain. This review emphasizes the need for personalized approaches and advanced technologies to develop effective antiaging interventions. By integrating current knowledge, this review provides a comprehensive framework that underscores the importance of targeting hypoxia‐induced pathways to enhance healthy aging and reduce the burden of age‐related diseases.